Aspartate aminotransferase to platelet ratio correlates with poor prognosis and metabolic alterations in Dabie bandavirus infection - Guo, Chunxia; Li, Ruixue; Wang, Xia; Peng, Xiulan (Frontiers in Immunology, 2025)
IntroductionSevere fever with thrombocytopenia syndrome (SFTS) is an emerging infectious disease with a high mortality rate caused by Dabie bandavirus. The aspartate aminotransferase to platelet ratio index (APRI) is a biomarker of liver injury and inflammation. This study aimed to examine the correlation between APRI and SFTS prognosis using clinical data analysis and attempt to explain its prognostic significance through metabolic analysis.MethodsData from hospitalized patients with a confirmed diagnosis of SFTS virus infection at Wuhan Union Hospital were retrospectively collected. The low and high APRI groups were 1:1 matched using propensity score matching (PSM) analysis. Fresh plasma was collected from patients with SFTS on admission and used for metabolic tests.ResultsA total of 617 patients with SFTS who met the inclusion criteria were selected for analysis. Survival analysis revealed that patients with SFTS with high APRI (> 35.3) had a substantially higher death rate than those with low APRI (≤ 35.3). Receiver operating characteristic analysis showed the predictive performance of APRI for SFTS prognosis is 0.77, with a 95% CI of 0.73–0.80, which was superior to NLR (area under the curve (AUC): 0.65), platelet-to-lymphocyte ratio (AUC: 0.54), and systemic immune-inflammation index (AUC: 0.58). The prognostic value and predictive performance of APRI were more substantial after PSM than before PSM. Metabolomic testing identified several differential serum metabolites, with alanine, aspartate, glutamate, glycerophospholipid, and tryptophan metabolism being the most important metabolic pathways.ConclusionA high APRI score was associated with relatively higher mortality in patients with SFTS, and its predictive performance for the survival outcome of SFTS was superior to that of well-recognized inflammatory scores. Alanine, aspartate, and glutamate metabolism are involved in the progression of SFTS.